Idiopathic dilated cardiomyopathy in children: Prognostic indicators - Mehmet Emre Arı; Tamer Yoldaş; Utku Arman Örün; Selmin Karademir (KARE Publishing, 2019)
Objective: Dilated cardiomyopathy (DCM) is a disorder featuring left ventricular dysfunction, heart failure, and a poor prognosis. The etiology is still unclear, despite diagnostic and therapeutic developments. This study was an evaluation of factors affecting the life span of a group of idiopathic DCM patients. Methods: A total of 79 patients from between October 2005 and October 2017 with a diagnosis of idiopathic DCM were evaluated retrospectively. Demographic characteristics, clinical information, left ventricular function, treatment, and follow-up of the patients were reviewed based on hospital records. Age, gender, parental consanguinity, cardiomegaly on telecardiography, reduced ejection fraction (EF) and shortening fraction (SF), degree of mitral regurgitation, and intracardiac thrombosis were determined to affect prognosis. Results: The patients were aged 20+-60 months, and the male/female ratio was 1.02/1. The patients most frequently presented with heart failure signs and symptoms (n=59, 74.7%). The most common physical examination findings were a murmur (n=53, 67.1%) and tachycardia (n=48, 60.8%). Cardiomegaly was observed on telecardiography in 73.4% of the patients. The EF and SF values were 35.7+-12.6% and 17.3+-6.5%, respectively. In all, 42 (53.2%) patients had mitral regurgitation of grade 2 or higher. The duration of follow-up was between 1 and 156 months (20+-34.9 months). Intracardiac thrombosis was detected in 4 (5.1%) patients. The mortality rate was 36.7%. When the prognostic factors were compared according to survival time, it was determined that survival was reduced in cases of parental consanguinity, low EF, and cardiomegaly. Conclusion: The most important negative markers affecting the length of survival of DCM patients were parental consanguinity, cardiomegaly detected on telecardiography, and a reduced EF level.